Supplier linkages of accommodation sector: the case of Manavgat in Turkey - Ferhan Gezici; Gizem Küçüksarý (European Regional Science Association (ERSA), 2012)
Realizing the significance and contribution of tourism sector to regional/local economy, has increased the number of studies which have been trying to analyse the impacts of tourism on economic development. Several approaches and methodologies have already been developed for this purpose. The economic impact analysis mostly focuses on the spending of tourists, however it is not easy not only because of the data availability, but also the reliability since the cycle of spending has become more complex in the economy. In this paper, accommodation sector has taken into consideration as one of the main components of tourism sector. Supply chains of accommodation units have examined in order to evaluate the demand of tourism, linkages among different economic sectors and regional-spatial impacts of these linkages. Manavgat which is one of the main concentration districts within Antalya (the Mediterranean region), has been selected as the case study. The number, the size, the period of being supplier and the location of suppliers are defined as the main factors based on the different branches of service and activities of accommodation sector. The findings of the analysis put forward that most of the suppliers are located in Antalya rather than Manavgat. Therefore the demand of accommodation sector could not create expected capacity for supply in Manavgat and the economic impacts remain relatively low within local economy.
Keywords: 330; tourism; accommodation; supply chain; economic impact; Turkey